Validation of a unit evaluation survey for capturing students' perceptions of teaching and learning: A comparison among Australian and Estonian higher education students - Kumpas-Lenk, K.; Tucker, Beatrice; Gupta, Ritu (Elsevier Ltd, 2014)
This study reveals the results of validating and implementing a student evaluation survey called eVALUate into the Estonian higher education context for the purpose of benchmarking and determining those factors that help and hinder students to achieve the intended learning outcomes. A comparison of the responses from Estonian and Australian students indicated that the factors that least helped students in their achievement of the learning outcomes were: in the Estonian case, student engagement with their learning and in Australian case, feedback on students' work. These results help to evaluate current teaching and learning practices within an outcomes-based paradigm and provide a comparison for self-improvement for the purpose of transforming higher education.